Projeto Brincadas: ações possíveis para criação do inédito viável e para uma práxis decolonial - Sarra, Luciana Kool Modesto (2023)
Society is experiencing a moment of transformation and rapprochement with the media, even more accelerated with the Covid-19 pandemic. However, they also tolerated inequalities, marked by intense social injustice. In this scenario, in 2020, the “Brincadas Extension Project: the viable unheard in times of crisis” appeared to support the social, cognitive, and emerging demands in Brazilian society. This research aims to investigate how one of the training proposals of the Brincadas Project, carried out on April 10, 2021, called “Afro-Brazilian Play: for an anti-racist education”, organized from Engaged Multiliteracy, can create the viable unheard, through play aiming at a decolonial praxis. The methodology of this study is based on Critical Collaboration Research in proposals that aim to transform those involved, and on Engaged Multiliteracy that is organized from the ideas of Vygotsky, Freire, and the Pedagogy of Multiliteracies, facilitated by playing. Participants in this research study from the Research Group Language in Activities in the School Context (GP-LACE) are students, families, teachers and managers of public and private schools, local and international Play partners. For data collection and selection, descriptions of the event were made, obtained from the data collected through the analysis of recordings via Zoom, which made up 3 hours of general room and plenary rooms, 1:48:15 of evaluation of Play; 1:26:42 of the live that discussed the experience with viewers of the Project's social networks, YouTube, and Facebook; in addition to planning records. Data analysis was carried out through the actions of critical reflection: describing, informing, confronting, and reconstructing. The results revealed that working with Brincar in the moments of immersion, emergence and insertion allowed the participants to create the viable unheard, from the involvement with the theme, from the construction and expansion of the repertoire, enabling transforming, welcoming actions, engaged with the Good Live for decision-making in the face of situations of injustice in life